Studio di mortalità in una fabbrica per la produzione di manufatti in cemento-amianto in provincia di Pavia / Asbestos cement factory in Broni (Pavia, Italy): a mortality study - Oddone, Enrico; Ferrante, Daniela; Cena, Tiziana; Tùnesi, Sara; Amendola, Plinio; Magnani, Corrado (La Medicina del Lavoro, 2014)
Summary «Asbestos cement factory in Broni (Pavia, Italy): a mortality study». Background: To date, no study has reported cause-specific Standardized Mortality Ratios (SMR) for asbestos-cement workers at a manufacturing establishment in Broni (Pavia, Italy). This site is among those specifically targeted by Italian Law for reclamation (SIN – Site of National Interest for remediation). Objectives: To provide cause-specific SMRs for asbestos-cement workers in the Broni (Pavia, Italy) factory, with particular regard to duration of employment and latency. Methods: Cause-specific SMRs for asbestos-cement workers (1296 workers hired since 1/1/1950 and with follow-up period 1/1/1970-30/06/2004: 1254 males and 42 females, 545 deaths, 523 males and 22 females) were calculated using the cause-specific mortality rates for the Lombardy Region. Similarly, for pleural and peritoneal mesothelioma and lung cancer among male workers, SMRs by duration of employment and latency were calculated. Results: Significantly increased SMRs were observed among male workers for pleural (SMR 17.99, 95% CI 11.75-26.36) and peritoneal (SMR 10.10, 95% CI 4.05-20.77) mesothelioma and lung cancer (SMR 1.26, 95% CI 1.02-1.55) and among female workers for pleural mesothelioma (SMR 68.90, 95% CI 8.33-248.90) and ovarian cancer (SMR 8.56, 95% CI 1.04-30.91). Only among male workers, was a significant risk trend observed for pleural mesothelioma by duration of employment and for lung cancer by latency. Significantly reduced SMRs were observed, among male workers for all causes of death, cardiovascular and respiratory diseases. Conclusions: The results of this cohort study showed increased SMRs for pleural and peritoneal mesothelioma and lung cancer among male workers and for pleural mesothelioma and ovarian cancer among female workers. These results are consistent with the literature data. Riassunto Introduzione: Nessun lavoro ad oggi ha riportato le stime di mortalità degli addetti alla produzione di manufatti in cemento-amianto presso lo stabilimento di Broni (Pavia), sito di interesse nazionale per le bonifiche (SIN). Obbiettivi: Produrre le stime di mortalità causa-specifica per i lavoratori addetti alla produzione di cemento-amianto nello stabilimento di Broni (Pavia), anche in relazione alle variabili temporali di durata dell’esposizione e latenza. Metodi: Sono stati calcolati i Rapporti Standardizzati di Mortalità (RSM) per le principali patologie tra i lavoratori addetti alla produzione di cemento-amianto (1296 assunti dal 1/1/1950 e con periodo di follow-up 01/01/1970-30/06/2004: 1254 uomini e 42 donne, 545 deceduti, 523 uomini e 22 donne) con l’utilizzo dei tassi di mortalità causa-specifici per la Regione Lombardia. Allo stesso modo, per i mesoteliomi e per il tumore del polmone sono stati calcolati anche i RSM per le variabili di durata dell’esposizione e latenza. Risultati: Significativi aumenti di RSM sono stati osservati per i mesoteliomi pleurico (RSM 17.99, IC 95% 11.75-26.36) e peritoneale (RSM 10.10, IC 95% 4.05-20.77) e il tumore del polmone (RSM 1.26, IC 95% 1.02-1.55) tra gli uomini e per il mesotelioma pleurico (RSM 68.90, IC 95% 8.33-248.90) e il cancro dell’ovaio (RSM 8.56, IC 95% 1.04-30.91) tra le donne. Nel sesso maschile, una relazione significativa con la durata dell’esposizione è stata osservata per il mesotelioma pleurico e con la latenza per il tumore del polmone. Significative riduzioni di RSM tra gli uomini si sono osservate per tutte le cause di decesso e per le patologie cardiovascolari e dell’apparato respiratorio. Conclusioni: I risultati dello studio di coorte mostrano eccessi di mortalità per tumore del polmone e mesoteliomi tra gli uomini e per mesotelioma pleurico e cancro dell’ovaio tra le donne. Questi risultati sono coerenti con i dati di letteratura.